2022
DOI: 10.1126/sciadv.abq7023
|View full text |Cite
|
Sign up to set email alerts
|

Widespread formation of toxic nitrated bisphenols indoors by heterogeneous reactions with HONO

Abstract: With numerous structurally diverse indoor contaminants, indoor transformation chemistry has been largely unexplored. Here, by integrating protein affinity purification and nontargeted mass spectrometry analysis (PUCA), we identified a substantial class of previously unrecognized indoor transformation products formed through gas-surface reactions with nitrous acid (HONO). Through the PUCA, we identified a noncommercial compound, nitrated bisphenol A (BPA), from house dust extracts strongly binding to estrogen-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 58 publications
(92 reference statements)
0
26
0
Order By: Relevance
“…Also, in laboratory aqueous phase studies, 3-methylcatechol was consumed when exposed to sodium nitrite under acidic conditions (pH 4.7) and the formation of 3-methylnitrocatechol was observed by liquid chromatography–UV absorption. , Interestingly, such aqueous nitration pathways are not limited to the production of nitroaromatics in the atmosphere. In a recent study of indoor dust, the same reaction is also observed heterogeneously with gas-phase HONO and bisphenols, producing more toxic nitrobisphenols . In the field of food chemistry, polyphenols, often found in grapes and tea, are considered good antioxidants for their nitrite scavenging ability …”
Section: Introductionmentioning
confidence: 85%
“…Also, in laboratory aqueous phase studies, 3-methylcatechol was consumed when exposed to sodium nitrite under acidic conditions (pH 4.7) and the formation of 3-methylnitrocatechol was observed by liquid chromatography–UV absorption. , Interestingly, such aqueous nitration pathways are not limited to the production of nitroaromatics in the atmosphere. In a recent study of indoor dust, the same reaction is also observed heterogeneously with gas-phase HONO and bisphenols, producing more toxic nitrobisphenols . In the field of food chemistry, polyphenols, often found in grapes and tea, are considered good antioxidants for their nitrite scavenging ability …”
Section: Introductionmentioning
confidence: 85%
“…As mentioned above, we have already successfully applied the APNA method to multiple proteins including NRs, bacterial proteins, and transporter proteins. Unexpectedly, we have found that a very small number of chemicals often contributed to the majority of bioactivity. For instance, hydrocarbon surfactants were recently identified as the predominant synthetic PPARγ ligands in sewage sludge and house dust, among >40,000 mass spectrometry features .…”
Section: Protein Affinity Purification With Nontargeted Analysis (Apn...mentioning
confidence: 90%
“…Similarly, we have identified 31 previously unknown polyfluoroalkyl ligands of the human liver fatty acid binding protein ( h L-FABP) from aqueous film-forming foam (AFFF) products and AFFF-contaminated surface waters (Figure b) through APNA . Another very intriguing example is the recent identification of nitro-bisphenol A (NO 2 –BPA) as a new estrogen related receptor γ (ERRγ) agonist in house dust (Figure c): with ERRγ as the “bait”, NO 2 –BPA was isolated from house dust extracts consisting of >20,000 mass spectrometry features . The chemical identity of the previously unknown ERRγ ligand, and its high binding affinity to ERRγ, was confirmed with a synthesized standard.…”
Section: Protein Affinity Purification With Nontargeted Analysis (Apn...mentioning
confidence: 95%
See 2 more Smart Citations